Why some women fail to give birth at health facilities: a qualitative study of women's perceptions of perinatal care from rural Southern Malawi - Kumbani Lily; Bjune Gunnar; Chirwa Ellen; Malata Address; Odland Jon Øyvind (BMC, 2013)
Abstract Background Despite Malawi government's policy to support women to deliver in health facilities with the assistance of skilled attendants, some women do not access this care. Objective The study explores the reasons why women delivered at home without skilled attendance despite receiving antenatal care at a health centre and their perceptions of perinatal care. Methods A descriptive study design with qualitative data collection and analysis methods. Data were collected through face-to-face in-depth interviews using a semi- structured interview guide that collected information on women's perception on perinatal care. A total of 12 in- depth interviews were conducted with women that had delivered at home in the period December 2010 to March 2011. The women were asked how they perceived the care they received from health workers before, during, and after delivery. Data were manually analyzed using thematic analysis. Results Onset of labor at night, rainy season, rapid labor, socio-cultural factors and health workers' attitudes were related to the women delivering at home. The participants were assisted in the delivery by traditional birth attendants, relatives or neighbors. Two women delivered alone. Most women went to the health facility the same day after delivery. Conclusions This study reveals beliefs about labor and delivery that need to be addressed through provision of appropriate perinatal information to raise community awareness. Even though, it is not easy to change cultural beliefs to convince women to use health facilities for deliveries. There is a need for further exploration of barriers that prevent women from accessing health care for better understanding and subsequently identification of optimal solutions with involvement of the communities themselves.